Attractive streetscape making pedestrians walk longer routes: the case of Kunitachi in Tokyo - Capitanio, Marco (Journal of Architecture and Urbanism, 2019)
There are manifold benefits of an increase in pedestrian movement, both in regard to societal and to personal wellbeing, and walkability is considered a major goal in urban design. However, it is methodologically complicated to ascertain to what extent streetscape features relating to comfort and pleasurability influence pedestrian behavior. Our hypothesis is that pedestrians, at the neighborhood scale, prefer more attractive routes even if they are longer than other possible and equally safe routes to reach a certain destination, independently of the presence of amenities. As a case study, we selected Kunitachi, an attractive city in Tokyo Prefecture, thus adding to the body of non-western empirical research on pedestrian preferences. By comparing two Space Syntax betweenness simulations of pedestrian routes – compulsory and optional – with an actual counting of pedestrian frequency on site, and with behavioral observations, we have established that simulations according to the principle of “shortest route” considerably differ from actual pedestrian frequency. Only by allowing a certain detour leeway, simulations showed a less pronounced discrepancy with reality. While further research is needed to confirm our results, this enquiry has demonstrated that, attractive streetscape features are part of the reason why local residents prefer pleasant and comfortable routes over shorter ones.